Project-Based Learning Model to Improve Students' Creativity in Biology Learning Media Courses Biology Education Study Program, Cenderawasih University - Ruth Megawati; Wachju Subchan; Supeno; I Ketut Mahardika (Postgraduate, University of Mataram, 2024)
The purpose of this study is to improve students' learning creativity through the application of the Project Based Learning (PjBL) learning model. This type of research is Classroom Action Research with four stages, namely planning, implementation, observation, and reflection. The research instrument uses observation sheets and learning outcome tests. Observations are carried out during learning, and learning outcome tests are given at the end of each cycle. Based on the results of the study, it was obtained in cycle 1 that the creativity indicator for fluent thinking was 37% in the less category; cycle II 60% in the good category, and cycle III 73% in the good category; then the flexible thinking indicator in cycle I was 36% in the less category, cycle II 65% in the good category, and cycle III 78% in the good category; original thinking indicator cycle I is 20% in the less category, cycle II 61% is in the good category and cycle III 75% in the good category; elaboration thinking indicator cycle I is 15% in the very less category, cycle II 57% in the sufficient category and cycle III 67% in the good category. Learning outcome data in cycle I is only 37% of students who completed, cycle II 60% of students who completed, and cycle III 78% of students who completed.